Lunge in youth fencing: analysis of the load on the lower limbs and differences in gender for the prevention of injuries - Sannicandro, I.; Piccinno, A.; Cataleta, R.; Maffione, E.; de Pascalis, S. (Archivos de medicina del deporte, 2008)
Introduction: Fencing is a sport which imposes different loads for both the upper and lower extremities. Being aware of the load imposed by the lunge gesture both for the push limb and for the one used for ground contact on one foot is useful to structure training sessions which are geared towards performance improvement as well as risk reduction (Bisciotti, 2007). As a matter of fact, ground contact on one foot potentially constitutes one of the most dangerous gestures for non contact articular knee traumas (Bisciotti, 2007;Louw et al., 2006). Aim: The work is determined to analyse the load imposed by the lunge gesture in youth fencing by highlighting the differences between the two limbs and, possibly, even differences in gender. Besides, the work is determined to observe if the specific load imposed by fencing gestuality can also condition the phases of a symmetrical gesture such as the counter movement jump. Materials and methods: The sample is represented by 44 athletes practising fencing: n males = 21, 15,8 ± 1,5yr, 175,3 ± 4,1cm, 70,1 ± 5,6kg.; n females = 13, 16,4 ± 1,9yr, 159,6 ± 4,8cm, 60,2 ±11,1kg. For the evaluation of the fencing lunge and jump using the Counter Movement Jump (CMJ) two dynamometric plates (Twin Plates, Globus Italia),and an accelerometer have been used, both supported by software to analyse the gesture. The statistic analysis has been carried out with the Wilcoxon test and its significance has been fixed at p <0.05 Discussion: The lunge can be described as gesture which requires substantial biomechanical differences for the two limbs. The push limb recruits the musculature with a concentric and explosive type of contraction highlighting average peak speeds of 2.7 m/sec for males and of 2,4 m/sec for females. The limb which supports the impact, although mainly relying upon a regime of stretch shortening cycle muscular contraction, must bear loads of over 1000N for males and around 835N for females. However, when these values are normalised because of body weight they do not highlight any difference between the two genders.; 1,4 times the body weight for both males and females during ground impact. The comparative analysis of the two genders highlights substantial differences in the execution of the lunge gesture in all of the other observed variables: there is therefore a need to envisage differentiated training for the two genders. The correlation between the values of the push limb during the specific gesture and those obtained with a cmj (r=0,67 p<0.01) and those between two force peaks obtained by two different gestures (r=0,64 con p<0.05) in the female group points out how the technique substantially influences the behaviour of the two limbs even in a symmetrical kind of gesture.